When Digital Finance Becomes a Gatekeeping System: Rethinking MSME Inclusion and Business Survival - Aliyya Aliyya; Hernanda Alfioni; Liana Mega Ristyani Bekti (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The digitalization of the financial sector is frequently framed as a technical solution to enhance financial inclusion and expand micro, small, and medium enterprises’ (MSMEs) access to capital. Through fintech platforms, digital payment systems, and data-driven credit assessments, digital finance is widely expected to reduce information asymmetry and lower entry barriers for small businesses. However, this perspective often assumes that expanded access automatically leads to stronger business resilience. This paper challenges that assumption by arguing that financial digitalization increasingly operates as a gatekeeping system that differentiates MSMEs based on their capacity to generate, manage, and comply with digital data requirements. While policy discussions commonly emphasize digital literacy and technological readiness, limited attention has been given to how algorithm-based evaluations, platform compliance standards, and data dependency reshape the conditions under which MSMEs are recognized as “bankable” or “investable.” A critical review of the literature suggests that participation in digital financial systems is not merely a matter of access, but of alignment with platform-defined metrics that implicitly privilege certain business behaviors while excluding others. As a result, many MSMEs do not reject digital finance in principle, but face heightened exposure to operational risk, opacity in decision-making processes, and uncertainty regarding their long-term position within platform-based financial ecosystems. This paper seeks to identify conceptual and policy gaps in existing discussions on financial digitalization and MSMEs by shifting the analytical focus from access expansion toward the structural role of digital finance in shaping business survival. By situating financial digitalization within a broader sustainable development framework, the study underscores the need for governance approaches that address digital gatekeeping and prevent financial inclusion from evolving into a new form of exclusion.